Exploratory Data Analysis of Exact Science and Social Science Learning Content on Digital Platform - Mambang - Mambang (Walisongo Journal of Information Technology, 2022)
Data is one of the essential aspects in providing new information and new knowledge so that the data exploration process can provide policies on a decision for many sectors. Exploratory Data Analysis in this paper begins with collecting datasets contained on the Youtube digital platform. The dataset used was 30 samples found on the top page of youtube in each keyword. After conducting the Exploratory Data Analysis process, we found new learning content on the digital youtube platform. From the Exploratory Data Analysis that has been carried out, we also find different variations of the analysis's variables. The duration variable shows the result that the total duration of the overall duration in mathematics learning content that includes the Exact Science field is less than the psychology learning content included in the Social Science field. Meanwhile, the overall number of views on mathematics learning content is more than the number of views on psychology learning content. From the collecting dataset that we have made, showing a considerable number of views is undoubtedly the key to equitable distribution of information and knowledge for all users. More innovation and creating learning content are expected to encourage increased human development.